Farm Household Economic Model of The Integrated Crop Livestock System: Conceptual and Empirical Study - Priyanti, Atien; Sinaga, B M; Syaukat, Y; Kuntjoro, S U (Indonesian Bulletin of Animal and Veterinary Sciences, 2007)
An integrated approach to enhance rice production in Indonesia is very prospectus throughout the implementation of adapted and liable integrated program. One of the challenges in rice crop sub sector is the stagnation of its production due to the limitation of organic matter availability. This provides an opportunity for livestock development to overcome the problems on land fertility through the use of manure as the source of organic fertilizer. Ministry of Agriculture had implemented a program on Increasing Integrated Rice Productivity with an Integrated Crop Livestock System as one of the potential components since 2002. Integrated crop livestock system program with special reference to rice field and beef cattle is an alternative to enhance the potential development of agriculture sector in Indonesia. The implementation on this integrated program is to enhance rice production and productivity through a system involving beef cattle with its goal on increasing farmersâ income. Household economic model can be used as one of the analysis to evaluate the success of the implemented crop livestock system program. The specificity of the farmers is that rationality behavior of the role as production and consumption decision making. In this case, farmers perform the production to meet home consumption based on the resources that used directly for its production. The economic analysis of farmers household can be described to anticipate policy options through this model. Factors influencing farmersâ decisions and direct interrelations to production and consumption aspects that have complex implications for the farmersâ welfare of the integrated crop livestock system program. Â  Key words: Farm household, economic model, integrated crop livestock system